3D hierarchical V–Ni-based nitride heterostructure as a highly efficient pH-universal electrocatalyst for the hydrogen evolution reaction. Issue 26 (17th June 2019) - Dong, Xue; Yan, Haijing; Jiao, Yanqing; Guo, Dezheng; Wu, Aiping; Yang, Ganceng; Shi, Xia; Tian, Chungui; Fu, Honggang
Abstract : A 3D hierarchical V–Ni-based nitride heterojunction anchored on carbon cloth (VN@Ni3 N–Ni/CC) was designed as a promising pH-universal hydrogen evolution reaction electrocatalyst. Abstract : Exploring inexpensive and efficient electrocatalysts for the hydrogen evolution reaction (HER) in a wide pH range is crucial for the development of sustainable energy applications. Herein, a novel 3D hierarchical V–Ni-based nitride heterojunction on carbon cloth (VN@Ni3 N–Ni/CC) was designed and fabricated as a promising pH-universal HER electrocatalyst through the controllable nitridation of the corresponding V–Ni–O/CC precursor. A series of experimental parameters were tested to adjust the nanostructure of the material and to gain insight into the relationship between its structure and activity. The VN@Ni3 N–Ni/CC sample produced under optimized conditions showed excellent catalytic activity and stability over a wide pH range with onset potentials of 8, 23 and 32 mV and Tafel slopes of 40, 97 and 79 mV dec −1 in 1.0 M KOH, 1.0 M PBS and 0.5 M H2 SO4 electrolytes, respectively. Notably, with regards to catalytic activity, our VN@Ni3 N–Ni/CC sample outperformed most currently available non-noble metal catalysts, and was also found to be superior to Pt–C/CC at certain current density intervals in alkaline and neutral media. The outstanding performance of VN@Ni3 N–Ni/CC was mainly attributed to the highly active heterointerfaces, excellent electronic conductivity and facilitated mass transport of its 3D hierarchical framework. We expect the results of this work to help in the design and engineering of other heterojunction materials based on hybrids of early- and late-transition metals, and hence yield materials that may be used as highly efficient catalysts for various applications.